Оценка влияния уровня биохимических показателей при развитии депрессивных расстройств - Павлова, Н. В.; Галайченко, Е. Н.; Бых, А. И. (НТУ "ХПИ", 2014)
Важную функцию в организме человека выполняет гормональная система. Она обеспечивает интеграцию функциональных систем и клеточной активности. Исследование состояния эндокринной системы при депрессивных расстройствах является одним из самых перспективных направлений биологической психиатрии и психонейроэндокринологии. Важными показателями гормонального баланса при депрессивных расстройствах является отношение уровня анаболических и катаболических гормонов. Установлено, что многие пациенты с депрессией имеют те или иные нарушения функций гипоталамо-гипофизарно-надпочечниковой системы.

In the human body the hormonal system performs the important function. It provides integration of functional systems and cellular activity. One of the most perspective directions of the biological psychiatry and psychoneuroendocrinology is research of the condition of endocrine system at depressive frustration. The relation of the level of anabolic and catabolic hormones is the important indicators of the hormonal balance at depressive frustration. Determined, that many patients with depression have those or other infringements of functions hypothalamo-pituitary-adrenal system. Possibility of complex analysis will greatly improve the reliability and usefulness from data, which we are getting. For these goals in the future is planned to build a biochemical model that will enhance the interpretation of t-ratings and as a result will make it possible to identify the first depressive episodes.
Estimation of the level influence of biochemical index at development of depressive frustration
Keywords: гормон анаболический; гормон катаболический; система гипоталамо-гипофизарно-надпочечниковая; biochemistry; depression; hormone anabolic; hormone catabolic